Symulacja konwekcji wymuszonej w przewodach prostoosiowych przy przepływie laminarnym metodą elementów brzegowych = Boundary elements method simulation of laminar flow forced convection in duct - Teleszewski, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the numerical algorithm Boundary Element Method to simulation modelling forced convection in a duct. The efficiency and the credibility of proposed algorithm were verified by numerical tests in theoretical solution. A numerical examples are presented fully developed forced convection through pentagon duct. In this study is proposed for determining the Nusselt number in regular polygonal channels.
Keywords: konwekcja wymuszona; przewody prostoosiowe; liczba Nusselta; metoda elementów brzegowych (MEB); forced convection; flow in ducts; Nusselt number; boundary element method (BEM)